Spatial variation of perceived equity and its determinants in a gateway community of Giant Panda National Park, China - Li, Qingyu; Huang, Junlong; Zhang, Yin; Gu, Guangcan; Brockington, Dan (Frontiers in Ecology and Evolution, 2023)
Social equity is essential in the governance of protected areas (PAs), as ignoring such consideration can lead to severe social resistance, which consequently risks jeopardizing conservation objectives. A central component of conservation equity will require understanding how equity varies across space, and the drivers of these differences. By questionnaire survey and kernel density analysis, we presented the spatial distribution patterns of perceived equity in a gateway community of Giant Panda National Park in China. The associations between spatial variables and locals’ fairness perceptions were further detected by applying geographically weighted regression (GWR). The results showed that: (1) The feelings for recognitional, procedural and distributional equity all displayed varied and distinctive spatial patterns among local dwellers; (2) While living inside PA boundary is more likely to be accompanied by negative recognitional feelings, the easy access to tourism spots is frequently linked with more positive procedural and distributional perceptions; (3) Surprisingly, the proximity to the PA authority decreases locals’ equitable judgements in all aspects, potentially due to the opaque participation channels. Guided by the theory of spatial justice, we argue that those spatial differentials in fairness perceptions are actually driven by the intrinsic discrepancy of biodiversity protection requirements and unevenly distributed management policies. Key steps to advance social equity goals include multi-industry guidance, extending participative channels and co-producing better compensation plans. Herein, this study appears to a greater focus on the spatial aspect of social equity issues in biodiversity conservation.